Hepatocellular adenoma, approximately half and predominantly inflammatory subtype, in 38 Japanese patients with several differences in age, gender, and clinical background factors from Western populations. Issue 3 (22nd February 2021) - Izu, Asami; Sugitani, Masahiko; Kinukawa, Noriko; Matsumura, Hiroshi; Ogawa, Masahiro; Moriyama, Mitsuhiko; Yamazaki, Shintaro; Takayama, Tadatoshi; Hano, Hiroshi; Yao, Takashi; Kanda, Hiroaki; Suzuki, Koyu; et al.
Abstract: Aim: Hepatocellular adenoma (HCA) has a lower prevalence in Japan than in Western countries and HCA subtypes have been reported for only a few Japanese patients. We analyzed HCA subtype data 38 patients from 23 hospitals in Japan in order to examine character and difference between Western countries. Methods: To confirm HCA and to analyze subtypes, we performed immunohistochemical examinations. Results: Thirty‐eight cases were found to have HCA without cirrhosis. The male/female ratio was 18/20. Ages ranged from 15 to 79 (average, 43.2) years. Male and elder patients are not rare, furthermore, most of elder patients are male. Glycogen storage disease, past history of medicament use, hepatitis B virus surface antigen‐positivity, antihepatitis C virus ‐positivity, diabetes mellitus, obesity, lipid metabolism disorder and alcoholism were present in of 6, 8, 1, 1, 6, 6, 4, and 6 cases, respectively. As to HCA subtypes, HNF1alpha‐inactivated HCA, beta‐catenin activated HCA (b‐HCA), inflammatory HCA (IHCA) and unclassified HCA (U‐HCA) accounted for nine (23.7%), four (10.5%), 17 (44.7%) and eight (21.1%) cases, respectively. Two cases showed coexistence of HCA and hepatocellular carcinoma (HCC) at surgery, and another had HCC which had been detected 23 years after HCA diagnosis. The HCA subtype of one of the former cases was U‐HCA, while the remaining two had b‐HCA and U‐HCA. Conclusions: In Japanese HCA cases, the proportions of U‐HCA, male and elder cases were slightly higher than in Western countries, and most of elder patients were male. IHCA was however common regardless of race, and was assumed to be the predominant subtype of HCA.